1990
DOI: 10.1002/ceat.270130120
|View full text |Cite
|
Sign up to set email alerts
|

Sodium compounds as catalysts for methanol dehydrogenation to water‐free formaldehyde

Abstract: Formaldehyde is produced industrially from methanol by partial oxidation or oxidative dehydrogenation. In these processes, water is formed as a by-product. Anhydrous formaldehyde is required for many syntheses and, therefore, its production is of potential interest. In the present study, catalysts based on alkali compounds were found to be active in the dehydrogenation of methanol in absence of oxygen. Sodium carbonate doped with indium shows a selectivity of up to 75% for methanol conversion not exceeding 60%. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 2 publications
1
13
0
1
Order By: Relevance
“…Generally, formaldehyde can be produced from methanol via an oxidative or a non‐oxidative pathway [Eq. ]: true20.166667emCH3OH+normalO220.166667emCH2normalO+20.166667emnormalH2normalO1.em0.166667em0.277778emΔf0.166667emH=-1590.166667emkJ0.166667emmol-1CH3OHCH2normalO+normalH21.em1.em1.em1.em1.em1.em0.166667em0.277778emΔf0.166667emH=+840.166667emkJ0.166667emmol-1 …”
Section: Introductionmentioning
confidence: 99%
“…Generally, formaldehyde can be produced from methanol via an oxidative or a non‐oxidative pathway [Eq. ]: true20.166667emCH3OH+normalO220.166667emCH2normalO+20.166667emnormalH2normalO1.em0.166667em0.277778emΔf0.166667emH=-1590.166667emkJ0.166667emmol-1CH3OHCH2normalO+normalH21.em1.em1.em1.em1.em1.em0.166667em0.277778emΔf0.166667emH=+840.166667emkJ0.166667emmol-1 …”
Section: Introductionmentioning
confidence: 99%
“…The volcano for CH 2 O production ( Fig. 4(d)) is similar to a lower right portion of the volcano for CH 3 O-H bond scission (Fig. 2(c)), indicating that the production of CH 2 O primarily proceeds through the CH 3 O-H path via a CH 3 O intermediate.…”
Section: Microkinetic Modelingmentioning
confidence: 74%
“…Ruf et al experimentally reported that without any catalyst, methanol could dehydrogenate to anhydrous CH 2 O at a very high temperature, 1173 K, with a CH 2 O yield being less than 20% and only 43% selective toward formaldehyde [7]. Anhydrous CH 2 O production from non-oxidative CH 3 OH dehydrogenation has been investigated on bulk and supported Ag, Zn, Cu, and Au catalysts [8][9][10][11][12][13][14][15][16], however, these catalysts were shown to deactivate a few hours. For instance, experimental work by Yamamoto et al reported that, a P-promoted CuO/SiO 2 catalyst with 50% CH 3 OH conversion and 80% CH 2 O selectivity, was partially deactivated over the course of 4 h, possibly due to sintering [9].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Many materials, including transition metal oxides, sodium carbonate, and zeolites, showed some activity in the title reaction. However, the results were not satisfactory due to their low conversion of methanol, low selectivity toward HCHO and/or the high reaction temperatures, about 800 or 900 • C [5][6][7][8][9][10][11]. Silver-based catalysts that are widely applied in the partial oxidation of methanol to HCHO [12][13][14][15] may be naturally a good choice for the process of the direct dehydrogenation of methanol, which our previous work has already proved to be possible [16,17].…”
Section: Introductionmentioning
confidence: 99%